Transforming climate science into usable services: The effectiveness of co-production in promoting uptake of climate information by smallholder farmers in Senegal - Chiputwa, Brian; Wainaina, Priscilla; Nakelse, Tebila; Makui, Parmutia; Zougmoré, Robert B.; Ndiaye, Ousmane; Minang, Peter A. (Elsevier, 2020)
Does the provision of weather and climate information services (WCIS) enhance farmer’s use of forecasts in informing farm decisions? This paper assesses the effectiveness of the Multi-disciplinary Working Group (MWG) – a WCIS co-production initiative in Senegal in influencing farmers uptake of weather and climate information (WCI). WCIS are increasingly gaining importance and widely touted as critical in helping farmers adapt to climate variability. While there have been various WCIS initiatives producing and translating climate data into tailored information and knowledge in different parts of the world, there is hardly any rigorous evidence assessing their effectiveness in improving uptake. In this assessment, we use innovative survey methods and apply rigorous analytical approaches that control for self-selection bias to establish causal linkages between the MWG and use of WCIS. Our findings indicate that MWGs are positively associated with farmers’ awareness, access and uptake of WCI resulting in farm management responses depending on the type of information used. The presence of MWGs generally increases farmer’s awareness of WCI by 18%, access by 12% and uptake by 10%. Furthermore, use of seasonal forecasts is generally associated with a higher proportion of farmers using improved seed, fertilizers and manure, but negatively with crop diversification within MWG locations. This suggests that participatory approaches in the provision of tailored climate information and advisory services can lead to higher uptake and use among farmers in informing farm management responses for better adaptation to climate change. We highlight lessons for improved evaluations of WCIS in future.